Perancangan Alat Pengayak Maggot Portable Sebagai Bentuk Penerapan Teknologi Tepat Guna Untuk UMKM dan Home Industry - Mutia, Karina Ayu; Ismiawati, Yuyun; Arsiwi, Pramudi (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economy but often face various challenges, such as limited capital, simple technology, and a low level of workforce education. One solution that can be implemented is Appropriate Technology (TTG), which aligns with local needs, is environmentally friendly and optimizes resource use. UMKM REPRO in Semarang, focusing on Black Soldier Fly (BSF) maggot cultivation, faces challenges in the sieving process, which is time-consuming and reduces production efficiency. A maggot sieving tool was developed using the Value Engineering method, emphasizing safety, ergonomics, and cost analysis to address this issue. This tool is expected to make the maggot sieving process more efficient and economical, with an estimated production cost of Rp 290,000. This innovation provides a practical and appropriate solution for MSMEs and home industries in the livestock sector. Keywords: Black Soldier Fly Maggots, MSMEs, Sieving Device, Value Engineering